Inordinate Glucose Variation Poststroke is Associated with Poor Neurological Improvement in Patients Without History of Diabetes. (17th March 2014) - Yu, Jian; Zhang, Cheng‐Guo; Zhang, Su‐Ping; Xiao, Wei‐Min; Pan, Xiao‐Ping; Liu, Zhen‐Hua; Chu, Xiao‐Fan; Gao, Qing‐Chun; Xu, An‐Ding; Xu, Zhi‐Qiang; Zeng, Jin‐Sheng
Summary Introduction Glucose variation is an important risk factor for the complications of diabetes mellitus. The plasma glucose level poststroke is in continuous fluctuation. However, whether the variation influences neurological improvement remains unknown. Aims This observational study aimed to investigate the association of glucose variation with neurological improvement poststroke. Methods We consecutively enrolled 216 ischemic stroke patients with no history of diabetes mellitus within 72 h of onset, with instant blood glucose <11.1 mmol/L at admission. The glucometabolic status was evaluated by an oral glucose tolerance test 1 day after admission and 14 days after stroke, respectively. The severity of neurological deficit was assessed with the National Institute of Health Stroke Scale (NIHSS). Results Fourteen days after stroke, 31% patients were found to have impaired glucose tolerance and 30.6% were newly diagnosed diabetes mellitus by oral glucose tolerance test. A higher level of instant blood glucose at admission or fasting plasma glucose (FPG) at 1 day correlated with a less neurological improvement. The number of patients with no <20% decrease in NIHSS was significantly decreased in patient group with higher than 30% variation of either FPG or 2‐h postprandial glucose. Similar correlation between glucose variation and neurological improvement was also found in 117 patients with 2‐h postprandial glucose ≥7.8 mmol/L at 1 day. Conclusions Inordinate glucose variation correlated with less neurological improvement poststroke, giving the evidence that the fluctuation of glucose levels in stroke patients should be taken into consideration during glucose modulation.